Hadron-quark phase transition in the neutron star with vector MIT bag model and Korea-IBS-Daegu-SKKU functional - Sen, Debashree; Gil, Hana; Hyun, Chang Ho (Frontiers in Astronomy and Space Sciences, 2024)
Employing the Korea-IBS-Daegu-SKKU (KIDS) density functional for the hadron phase and the MIT bag model with vector (vBag) model for the quark phase, we obtain hadron-quark phase transition in neutron stars considering Maxwell construction. The structural properties of the resultant hybrid stars are computed for three different values of bag constant (B) in the range B1/4=145−160 MeV). We study the effects of symmetry energy (J) on the hybrid star properties with the different KIDS model and found that J has important influence not only on the transition properties like the transition mass, transition radius and jump in density due to phase transition, but also on the stability of the hybrid stars. The vector repulsion of the quark phase via the parameter GV has profound influence in obtaining reasonable hybrid star configurations, consistent with the recent astrophysical constraints on the structural properties of compact stars. Within the aforesaid range of B, the value of GV is constrained to be 0.3 ≲GV≲ 0.4 in order to obtain reasonable hybrid star configurations.